Antifreeze and drought-resistant sand-fixing material and preparation method thereof

By adding glycerin to acetic acid cellulose sandwater fixing agent in amino silicane, enhances its anti-freezing performance, solves the problem of freezing the existing sandwiches in low temperature environments, and prepares a low-temperature anti-freezing anti-freezing anti-frozen freezing frozen freezer suitable for high-cold sandy land applicable to the Qinghai-Tibet Plateau Solid material.

CN116622379BActive Publication Date: 2025-01-28NORTHWEST INST OF ECO ENVIRONMENT & RESOURCES CAS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310572418.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-19
Publication Date
2025-01-28
Estimated Expiration
2043-05-19

AI Technical Summary

Technical Problem

The existing aminosilane coupling agent - cellulose acetate sand fixing agent has poor freezing resistance under low temperature environments and is difficult to be suitable for the high-cold sands of the Qinghai-Tibet Plateau.

Method used

By adding glycerin antifreeze to targeted SCA-CA sand fixing agent, it reacts with acetic acid cellulose and Silicane coupling agent, enhances its antifreeze performance, and prepares glycerin modifiers in high-cold regions- Gly-SCA-CA fixing material.

Benefits of technology

It significantly improves the anti -freezing performance of sand fixing materials in low temperature environments, ensures that its stable solidification and pressure resistance in high -cold areas are suitable for sand fixing applications in high -cold sandy land in the Qinghai -Tibet Plateau.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116622379B_ABST
    Figure CN116622379B_ABST
Patent Text Reader

Abstract

The present invention discloses an antifreeze and drought-resistant sand-fixing material and a preparation method thereof. The preparation method of the antifreeze and drought-resistant sand-fixing material comprises: mixing cellulose acetate and an aminosilane coupling agent solution, and subjecting the obtained mixed system to vacuum heat treatment; then adjusting the pH value of the mixed system to neutral, and then adding glycerol to prepare the antifreeze and drought-resistant sand-fixing material. The present invention adopts glycerol antifreeze agent to directionally regulate SCA-CA sand-fixing agent. Glycerol can react with hydroxyl groups in cellulose acetate, and can also be miscible with silane coupling agent, so that silane coupling agent-cellulose acetate has good antifreeze performance, and prepares low-temperature resistant, antifreeze and drought-resistant glycerol-modified silane coupling agent-cellulose acetate (GLY-SCA-CA) sand-fixing material suitable for high-cold sandy land on the Qinghai-Tibet Plateau.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a sand-fixing material, in particular to a glycerol-modified silane coupling agent-cellulose acetate (GLY-SCA-CA) low-temperature-resistant, antifreeze-resistant and drought-resistant sand-fixing material and a preparation method and use thereof, belonging to the technical field of biopolymers and sand-fixing. Background Art

[0002] Desertification seriously threatens global ecological security and the sustainable development of human economy and society, affects 25% of the world's total land area, and threatens the lives of more than 1 billion people in more than 100 countries. It is a major environmental problem and development bottleneck facing the world, and China is one of the countries seriously harmed by desertification. Wind and sand activities are typical surface processes in desert areas. Therefore, it is of great significance to take necessary measures to prevent wind and sand and block sand.

[0003] The carbonyl group on the aminosilane coupling agent-cellulose acetate (SCA-CA) sand-fixing agent chain can react with inorganic ions in the sand to achieve sand fixation. After CA is treated with aminosilane coupling agent, its solution stability, curing strength, and water absorption and retention properties can be enhanced, which can be used as a sand fixation measure in arid desert areas. However, its low temperature resistance is poor.

[0004] The environment of the alpine sandy land in the Qinghai-Tibet Plateau is dry and low-temperature all year round. The surface soil of the alpine sandy land in the Qinghai-Tibet Plateau is mainly alpine meadow soil, and the sandy areas are mainly wind-blown sandy soil. The sand-fixing agent suitable for this area needs to have good low-temperature resistance and anti-freeze performance. Therefore, it is necessary to carry out targeted regulation and modification of the silane coupling agent-cellulose acetate (SCA-CA) sand-fixing agent to enhance its low-temperature resistance, which has also become an urgent problem for industry researchers to solve. Summary of the invention

[0005] The purpose of the present invention is to provide a low temperature resistant, antifreeze and drought resistant sand-fixing material suitable for high-cold sandy land in the Qinghai-Tibet Plateau, so as to improve the antifreeze and drought resistant sand-fixing material in the prior art.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0007] The embodiment of the present invention provides a method for preparing an antifreeze and drought-resistant sand-fixing material, which comprises:

[0008] Mixing cellulose acetate and aminosilane coupling agent solution, and subjecting the obtained mixed system to vacuum heat treatment;

[0009] Then the pH value of the mixed system is adjusted to be neutral, and glycerin is added to obtain the antifreeze and drought-resistant sand-fixing material.

[0010] In some embodiments, the aminosilane coupling agent used in the present invention includes any one or a combination of two or more of 3-aminopropyldiethoxymethylsilane, γ-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, etc.

[0011] The embodiment of the present invention further provides an antifreeze and drought-resistant sand-fixing material, which is prepared by the above-mentioned preparation method.

[0012] Furthermore, the embodiments of the present invention also provide the application of the aforementioned antifreeze and drought-resistant sand-fixing material in the field of sand fixation in high-cold areas.

[0013] Compared with the prior art, the beneficial effects of the present invention are:

[0014] The present invention adopts glycerol antifreeze agent to directionally regulate SCA-CA sand-fixing agent. Glycerol can react with hydroxyl groups in cellulose acetate and can also be compatible with silane coupling agent, so that silane coupling agent-cellulose acetate has good antifreeze performance, and prepares low-temperature resistant, antifreeze and drought-resistant glycerol-modified silane coupling agent-cellulose acetate (GLY-SCA-CA) sand-fixing material suitable for high-cold sandy land in the Qinghai-Tibet Plateau. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 It is a schematic diagram of the preparation of a glycerol-modified silane coupling agent-cellulose acetate (GLY-SCA-CA) low-temperature-resistant, antifreeze-resistant, and drought-resistant sand-fixing material in a typical embodiment of the present invention. DETAILED DESCRIPTION

[0017] In view of the problem of poor low-temperature resistance of SCA-CA sand-fixing agent, the inventors have proposed the technical solution of the present invention after long-term research and extensive practice, which mainly uses glycerol antifreeze to directionally regulate the SCA-CA sand-fixing agent to prepare a low-temperature and drought-resistant GLY-SCA-CA sand-fixing agent suitable for the high-cold sandy land of the Qinghai-Tibet Plateau. The technical solution, its implementation process and principles will be further explained as follows. However, it should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described below (Examples) can be combined with each other to form a new or preferred technical solution. Due to space limitations, they will not be described one by one here.

[0018] As another aspect of the technical solution of the present invention, a method for preparing a glycerol-modified silane coupling agent-cellulose acetate (GLY-SCA-CA) low-temperature resistant, antifreeze and drought resistant sand-fixing material is provided, comprising:

[0019] Mixing cellulose acetate and aminosilane coupling agent solution, and subjecting the obtained mixed system to vacuum heat treatment;

[0020] Then the pH value of the mixed system is adjusted to be neutral, and glycerin is added to obtain the antifreeze and drought-resistant sand-fixing material.

[0021] The preparation mechanism of the present invention is that glycerin (GLY) is an effective non-toxic antifreeze agent, which can react with the hydroxyl group in cellulose acetate and can also be miscible with the silane coupling agent, so that the antifreeze agent glycerin can enhance the low temperature resistance of the aminosilane coupling agent-cellulose acetate (SCA-CA) sand-fixing agent, so that the silane coupling agent-cellulose acetate has good antifreeze performance and can be used as a sand-fixing measure for the alpine sandy land on the Qinghai-Tibet Plateau.

[0022] At the same time, the amino (-NH2) group in the silane coupling agent (SCA) can interact with the polar carbonyl (-CO) and oxycarbonyl (-COO) of CA, and the silicon in the aminosilane coupling agent also covalently bonds to the hydroxyl group of CA through the oxygen atom to form a silanized surface, thereby preparing a structurally stable and viscous hydrophilic liquid. When used for sand fixation, the aminosilane coupling agent can enhance the solution stability, curing strength and water absorption and water retention of CA after treatment. Its carbonyl group can react with inorganic ions in the sand to enhance sand fixation.

[0023] The degree of substitution of the cellulose acetate used in the present invention is 1.6 to 2.5.

[0024] In some embodiments, the aminosilane coupling agent in the aminosilane coupling agent solution of the present invention can be any one or a combination of two or more of 3-aminopropyldiethoxymethylsilane (APDEMS, KH902), γ-aminopropyltriethoxysilane (APTES, KH550), N-2-aminoethyl-3-aminopropyltrimethoxysilane (KH792), etc., but is not limited thereto.

[0025] In some embodiments, the aminosilane coupling agent solution includes a mixture of an aminosilane coupling agent and a selected solvent.

[0026] Furthermore, the selected solvent may be a combination of ethanol and water, wherein the mass ratio of ethanol to water is in the range of 2:1 to 4:1 w / w.

[0027] Furthermore, the content of the aminosilane coupling agent in the aminosilane coupling agent solution is 2 wt % to 95 wt %.

[0028] In some embodiments, the molar ratio of the aminosilane coupling agent to cellulose acetate in the aminosilane coupling agent solution is 0.5 to 2:1, that is, the amount of the aminosilane coupling agent added relative to cellulose acetate (the molar ratio to cellulose acetate) can be 0.5:1, 1:1, 1.5:1, 2:1, etc.

[0029] In some embodiments, the preparation steps of the present invention further include: mixing cellulose acetate, aminosilane coupling agent solution, and hydrochloric acid to adjust the pH value of the mixed system to 3, or adding HCl to the mixed system to adjust the pH value to 3.

[0030] As one of the preferred schemes, the temperature of the vacuum heat treatment is 110°C to 160°C, for example, it can be 115°C, 125°C or 160°C, and the time is 1 to 3 hours, for example, it can be 1 hour, 1.5 hours, 3 hours, etc.

[0031] As one of the preferred schemes, the preparation method further specifically includes: adding a glycerol solution to a mixed system with a neutral pH value, and mixing and reacting at 20-30°C for 24h-48h to obtain an antifreeze, drought-resistant and sand-fixing material, wherein the molar percentage of the glycerol solution to the aminosilane coupling agent is 50-100%, for example, it can be 50%, 100%, etc.

[0032] Furthermore, the volume of the glycerol solution can be 20 mL, 30 mL, 40 mL, 50 mL, 60 mL, etc.

[0033] Another aspect of the embodiments of the present invention further provides an antifreeze and drought-resistant sand-fixing material prepared by the aforementioned preparation method.

[0034] According to the test, after curing for 8 hours, the antifreeze and drought-resistant sand-fixing material of the present invention has a bonding strength of 4 to 6 MPa at liquid nitrogen temperature (-210 to -196°C) and a water permeability coefficient of 5x10 -4 cm / s~1.5x10 -3 cm / s, and the compressive strength of the sand-fixing samples is between 4.5 and 6.5 MPa.

[0035] Correspondingly, another aspect of the embodiments of the present invention further provides the use of any of the aforementioned glycerol-modified silane coupling agent-cellulose acetate (GLY-SCA-CA) low-temperature resistant, antifreeze and drought-resistant sand-fixing materials in the field of sand fixation in high-cold areas.

[0036] Through the above technical scheme, the present invention adopts glycerol antifreeze agent to directionally regulate SCA-CA sand-fixing agent. Glycerol can react with hydroxyl groups in cellulose acetate and can also be soluble in silane coupling agent, so that silane coupling agent-cellulose acetate has good antifreeze performance, and prepares low-temperature resistant, antifreeze and drought-resistant glycerol-modified silane coupling agent-cellulose acetate (GLY-SCA-CA) sand-fixing material suitable for the high-cold sandy land of the Qinghai-Tibet Plateau.

[0037] In order to make the purpose, technical scheme and application of the present invention clearer, the technical scheme of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. The described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. The implementation conditions used in the following embodiments can be further adjusted according to actual needs, and the unspecified implementation conditions are usually the conditions in conventional experiments.

[0038] Example 1

[0039] 20g of cellulose acetate (substitution degree of 1.6-2.2) was added to an aminosilane coupling agent (N-2-aminoethyl-3-aminopropyltrimethoxysilane) solution (ethanol / water: 80 / 20, w / w), the molar ratio of aminosilane coupling agent to cellulose acetate was 1:1, HCl was added, pH was adjusted to 3, stirred for 3h, vacuum heat treated at 110°C for 1h, and then distilled water was added to adjust the pH value to neutral. 40mL of 50% (molar percentage of aminosilane coupling agent) glycerol solution was added, and gently shaken at 25°C for 24h to obtain glycerol / silane coupling agent / cellulose acetate sand fixation material (GLY-SCA-CA), and the reaction process is as follows: Figure 1 The sand fixation specimens are of the size of 7.07m x 7.07m x 7.07m, with at least 3 specimens in each group.

[0040] Example 2

[0041] 20g of cellulose acetate (substitution degree of 2.2-2.5) was added to an aminosilane coupling agent (N-2-aminoethyl-3-aminopropyltrimethoxysilane) solution (ethanol / water: 80 / 40, w / w), the molar ratio of aminosilane coupling agent to cellulose acetate was 1:1, HCl was added, pH was adjusted to 3, stirred for 3h, vacuum heat treated at 110°C for 1h, and then distilled water was added to adjust the pH value to neutral. 40mL of 50% (molar percentage of aminosilane coupling agent) glycerol solution was added, and gently shaken at 25°C for 24h to obtain glycerol / silane coupling agent / cellulose acetate sand fixation material (GLY-SCA-CA), and the reaction process is as follows: Figure 1The sand fixation specimens are of the size of 7.07m x 7.07m x 7.07m, with at least 3 specimens in each group.

[0042] The inventors of this case also tested the antifreeze performance, water solubility and other properties of the sand-fixing material obtained in this embodiment, and the results are as follows:

[0043] In Example 1, after the antifreeze and drought-resistant sand-fixing material was cured for 8 hours, the bonding strength at liquid nitrogen temperature (-210 to -196°C) was 4 MPa, and the water permeability coefficient was 1.5x10 -3 cm / s, and the compressive strength of the sand-fixing sample is 4.5MPa.

[0044] In Example 2, after the antifreeze and drought-resistant sand-fixing material was cured for 8 hours, the bonding strength at liquid nitrogen temperature (-210 to -196°C) was 5 MPa, and the water permeability coefficient was 1x10 -3 cm / s, and the compressive strength of the sand-fixing sample is 5.5MPa.

[0045] Example 3

[0046] 20g of cellulose acetate (substitution degree of 2.2-2.5) was added to an aminosilane coupling agent (N-2-aminoethyl-3-aminopropyltrimethoxysilane) solution (ethanol / water: 80 / 20, w / w), the molar ratio of aminosilane coupling agent to cellulose acetate was 0.5:1, HCl was added, pH was adjusted to 3, stirred for 3h, vacuum heat treated at 110°C for 1h, and then distilled water was added to adjust the pH value to neutral. 40mL of 50% glycerol solution (molar percentage of aminosilane coupling agent) was added, and gently shaken at 25°C for 24h to obtain glycerol / silane coupling agent / cellulose acetate sand fixation material (GLY-SCA-CA), and the reaction process is as follows: Figure 1 The sand fixation specimens are of the size of 7.07m x 7.07m x 7.07m, with at least 3 specimens in each group.

[0047] Example 4

[0048] 20g of cellulose acetate (substitution degree of 2.2-2.5) was added to an aminosilane coupling agent (N-2-aminoethyl-3-aminopropyltrimethoxysilane) solution (ethanol / water: 80 / 20, w / w), the molar ratio of aminosilane coupling agent to cellulose acetate was 1:1, HCl was added, pH was adjusted to 3, stirred for 3h, vacuum heat treated at 110°C for 1h, and then distilled water was added to adjust the pH value to neutral. 40mL of 60% glycerol solution (molar percentage of aminosilane coupling agent) was added, and gently shaken at 25°C for 24h to obtain glycerol / silane coupling agent / cellulose acetate sand fixation material (GLY-SCA-CA), and the reaction process is as follows: Figure 1The sand fixation specimens are of the size of 7.07m x 7.07m x 7.07m, with at least 3 specimens in each group.

[0049] Example 5

[0050] 20g of cellulose acetate (substitution degree of 2.2-2.5) was added to an aminosilane coupling agent (N-2-aminoethyl-3-aminopropyltrimethoxysilane) solution (ethanol / water: 80 / 20, w / w), the molar ratio of silane coupling agent to cellulose acetate was 2:1, HCl was added, pH was adjusted to 3, stirred for 3h, vacuum heat treated at 110°C for 1h, and then distilled water was added to adjust the pH value to neutral. 40mL of 50% glycerol solution (molar percentage of aminosilane coupling agent) was added, and gently shaken at 25°C for 24h to obtain glycerol / silane coupling agent / cellulose acetate sand fixation material (GLY-SCA-CA), and the reaction process is as follows: Figure 1 The sand fixation specimens are of the size of 7.07m x 7.07m x 7.07m, with at least 3 specimens in each group.

[0051] The inventors of this case also tested the antifreeze performance, water solubility and other properties of the sand-fixing material obtained in this embodiment, and the results are as follows:

[0052] In Example 3, after the antifreeze and drought-resistant sand-fixing material was cured for 8 hours, the bonding strength at liquid nitrogen temperature (-210 to -196°C) was 5 MPa, and the water permeability coefficient was 1.5x10 -3 cm / s, and the compressive strength of the sand-fixing sample is 5MPa.

[0053] In Example 4, after the antifreeze and drought-resistant sand-fixing material was cured for 8 hours, the bonding strength at liquid nitrogen temperature (-210 to -196°C) was 5.5 MPa, and the water permeability coefficient was 1x10 -3 cm / s, and the compressive strength of the sand-fixing sample is 6MPa.

[0054] In Example 5, after curing for 8 hours, the antifreeze and drought-resistant sand-fixing material has a bonding strength of 6 MPa at liquid nitrogen temperature (-210 to -196°C) and a water permeability coefficient of 5x10 -4 cm / s, and the compressive strength of the sand-fixing sample is 6.5MPa.

[0055] Example 6

[0056] 20g of cellulose acetate (substitution degree of 2.2-2.5) was added to an aminosilane coupling agent (N-2-aminoethyl-3-aminopropyltrimethoxysilane) solution (ethanol / water: 80 / 20, w / w), the molar ratio of aminosilane coupling agent to cellulose acetate was 1:1, HCl was added, pH was adjusted to 3, stirred for 3h, vacuum heat treated at 110°C for 3h, and then distilled water was added to adjust the pH value to neutral. 40mL of 100% glycerol solution (molar percentage of aminosilane coupling agent) was added, and gently shaken at 25°C for 24h to obtain glycerol / silane coupling agent / cellulose acetate sand fixation material (GLY-SCA-CA), and the reaction process is as follows: Figure 1 The sand fixation specimens are of the size of 7.07m x 7.07m x 7.07m, with at least 3 specimens in each group.

[0057] Example 7

[0058] 20g of cellulose acetate (substitution degree of 2.2-2.5) was added to an aminosilane coupling agent (3-aminopropyldiethoxymethylsilane) solution (ethanol / water: 80 / 20, w / w), the molar ratio of aminosilane coupling agent to cellulose acetate was 1:1, HCl was added, pH was adjusted to 3, stirred for 3h, vacuum heat treated at 130°C for 2h, and then distilled water was added to adjust the pH value to neutral. 40mL of 50% glycerol solution (molar percentage of aminosilane coupling agent) was added, and gently shaken at 20°C for 48h to obtain glycerol / silane coupling agent / cellulose acetate sand fixation material (GLY-SCA-CA), and the reaction process is as follows: Figure 1 The sand fixation specimens are of the size of 7.07m x 7.07m x 7.07m, with at least 3 specimens in each group.

[0059] Example 8

[0060] 20g of cellulose acetate (substitution degree of 2.2-2.5) was added to an aminosilane coupling agent (γ-aminopropyltriethoxysilane) solution (ethanol / water: 80 / 30, w / w), the molar ratio of aminosilane coupling agent to cellulose acetate was 1:1, HCl was added, pH was adjusted to 3, stirred for 3h, vacuum heat treated at 160℃ for 1h, and then distilled water was added to adjust the pH value to neutral. 40mL of 50% glycerol solution (molar percentage of aminosilane coupling agent) was added, and gently shaken at 30℃ for 36h to obtain glycerol / silane coupling agent / cellulose acetate sand fixation material (GLY-SCA-CA), and the reaction process is as follows: Figure 1 The sand fixation specimens are of the size of 7.07m x 7.07m x 7.07m, with at least 3 specimens in each group.

[0061] The inventors of this case also tested the antifreeze performance, water solubility and other properties of the sand-fixing material obtained in this embodiment, and the results are as follows:

[0062] In Example 6, after the antifreeze and drought-resistant sand-fixing material was cured for 8 hours, the bonding strength at liquid nitrogen temperature (-210 to -196°C) was 4 MPa, and the water permeability coefficient was 1x10 -3 cm / s, and the compressive strength of the sand-fixing sample is 4.5MPa.

[0063] In Example 7, after the antifreeze and drought-resistant sand-fixing material was cured for 8 hours, the bonding strength at liquid nitrogen temperature (-210 to -196°C) was 4.5 MPa, and the water permeability coefficient was 7x10 -4 cm / s, and the compressive strength of the sand-fixing sample is 5MPa.

[0064] In Example 8, after the antifreeze and drought-resistant sand-fixing material was cured for 8 hours, the bonding strength at liquid nitrogen temperature (-210 to -196°C) was 5 MPa, and the water permeability coefficient was 5x10 -4 cm / s, and the compressive strength of the sand-fixing sample is 6MPa.

[0065] Comparative Example 1

[0066] Weigh 20g CA and dissolve it in 150g methyl acetate to prepare CA solution, add 40mL 50% glycerol solution, and gently shake at 25℃ for 24h. Compared with Example 1, this comparative example differs in that no aminosilane coupling agent is added. The sand fixation specimens are 7.07m x7.07m x7.07m in size, with at least 3 specimens per group. After curing for 8h, the antifreeze and drought-resistant sand fixation material has a bonding strength of 3.8MPa at liquid nitrogen temperature (-210~-196℃), and a water permeability coefficient of 1x 10 -3 cm / s, and the compressive strength of the sand-fixing sample is 3MPa.

[0067] Comparative Example 2

[0068] Compared with Example 1, this comparative example differs in that no glycerol is added. The sand fixation specimens are 7.07m x 7.07m x 7.07m in size, with at least 3 specimens in each group. After curing for 8 hours, the obtained antifreeze and drought-resistant sand fixation material has a bonding strength of 3MPa at liquid nitrogen temperature (-210 to -196°C) and a water permeability coefficient of 1x10 -3 cm / s, and the compressive strength of the sand-fixing sample is 3.4MPa.

[0069] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0070] It should be understood that the above examples are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an antifreeze and drought-resistant sand-fixing material, characterized in that: include: Mixing cellulose acetate, an aminosilane coupling agent solution, and hydrochloric acid to adjust the pH value of the obtained mixed system to 3, and subjecting the obtained mixed system to vacuum heat treatment, wherein the aminosilane coupling agent solution comprises a mixture of an aminosilane coupling agent and a selected solvent, wherein the aminosilane coupling agent is selected from any one or a combination of two or more of 3-aminopropyldiethoxymethylsilane, γ-aminopropyltriethoxysilane, and N-2-aminoethyl-3-aminopropyltrimethoxysilane, the content of the aminosilane coupling agent in the aminosilane coupling agent solution is 2 wt% to 95 wt%, the molar ratio of the aminosilane coupling agent to the cellulose acetate is 0.5 to 2:1, and the degree of substitution of the cellulose acetate is 1.6 to 2.5; The pH value of the mixed system is then adjusted to neutral, and a glycerol solution is added to prepare an antifreeze and drought-resistant sand-fixing material, wherein the molar percentage of the glycerol solution to the aminosilane coupling agent is 50-100%.

2. The preparation method according to claim 1, wherein: The selected solvent includes a combination of ethanol and water, wherein the mass ratio of ethanol to water is 2:1 to 4:1 w / w.

3. The preparation method according to claim 1, wherein: The vacuum heat treatment is performed at a temperature of 110° C. to 160° C. for 1 to 3 hours.

4. The preparation method according to claim 1, wherein include: A glycerol solution was added to a mixed system with a neutral pH value, and the mixture was reacted at 20-30°C for 24-48 hours to obtain an antifreeze and drought-resistant sand-fixing material.

5. A freeze-proof and drought-resistant sand-fixing material, characterized by: The invention is prepared by the preparation method according to any one of claims 1 to 4.

6. The antifreeze and drought-resistant sand-fixing material according to claim 5, characterized in that: After curing for 8 hours, the antifreeze and drought-resistant sand-fixing material has a bonding strength of 4 to 6 MPa at a liquid nitrogen temperature of -210 to -196°C and a water permeability coefficient of 5 x 10 -4 cm / s ~ 1.5 ⅹ 10 -3 cm / s, and the compressive strength of the sand-fixing samples is between 4.5 and 6.5 MPa.

Citation Information

Patent Citations

  • Chemical sand fixing agent and preparation method thereof

    CN102127453A

  • Cold-resistant low-temperature-resistant waterproof leak-stopping mortar and preparation method thereof

    CN107337406A